EXPLORING THE POSSIBILITY OF TAX INCENTIVE POLICIES IN INDONESIAN FOOTBALL INDUSTRY: BASED ON SWOT ANALYSIS APPROACH AND COMPANY FINANCIAL STATEMENTS - Hambali, Mohamad Luhur; Johan, Andi Mohammad (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2024)
This research aims to explore the possibility of implementing tax incentive policies in the Indonesian football industry based on the perspective of SWOT analysis and Company Financial Statements. Using the constructivism paradigm with a qualitative approach, this research was conducted using qualitative data collection techniques, with in-depth interviews with relevant agencies, such as the Indonesian Directorate General of Tax, Indonesian Fiscal Policy Agency, Indonesian Football League Operators, and Taxation Practitioners, as well as literature studies, using both primary and secondary data. The research concluded that based on the Company Financial Statements of sampling companies stated that Indonesian Football Industries suffers huge loss operation and need more investments. From SWOT Analysis many revenue sectors can still be optimized in this industry, by adjusting the financing conditions with existing revenues, so as not to experience losses. The football industry is currently deemed unable to enjoy tax incentive policies, both in terms of Direct Tax and Indirect Tax, due to the immaturity of this industry, and needs special strategies to optimize existing potential, such as implementing Public Private Partnership activities, optimizing the potential of existing Human Resources and Capital, better synchronization of technical and non-technical policies, and reconstructing future schedular taxation policies for this industry.